Investigation of the machinability of Inconel 718 in room temperature and preheated conditions - Amin, A. K. M. Nurul; Majed, A. Fakhruzi; Daud, M. K.; Patwari, Md Anayet Ullah; Ishtiyaq, M. H. (Trans Tech Publications Ltd., Switzerland, 2011)
Inconel 718 is widely used in the aviation, space, navigation and shipping industries because of its outstanding properties. The very mechanical characteristics that give this alloy the highly valued properties also make it one of the most difficult-to-machine aerospace materials. Due to the hardness of nickel-based super-alloys, such as Inconel 718, advanced tools like ceramics have been recommended to machine them. But ceramics are low conductive materials, and the heat generated during the machining of Inconel 718 transfers very slowly through them. The accumulation of generated heat on the cutting edges of ceramic tools causes many problems and sometime leads to premature tool failure. Hence in this study the effectiveness of PVD TiAlN coated carbide insert has been investigated. One approach to overcome the difficulties in machining of Inconel 718 is to use an external heat source to soften the work material surface layer to be removed in order to decrease its tensile strength. A new approach of preheating using inducting heating as an economical alternative to Laser Assisted Machining for end milling of Inconel 718 is presented in this paper. The machinability of Inconel 718 under varying conditions is evaluated by examining tool wear, surface roughness and chip morphology. With increasing work-piece preheating temperature, from room temperature to 420 ºC, the advantages of Induction heating is demonstrated by an extended tool life and better surface finish due to more stable chip formation and elimination of micro and macro failure of the tool.